2018
DOI: 10.1038/s41370-018-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate metabolite exposures among immigrants living in the United States: findings from NHANES, 1999–2014

Abstract: Phthalates exposure has been linked to multiple health risks, and US immigrants may have different exposures to phthalates due to lifestyle differences. Urinary concentrations of eight phthalate metabolites (mono-ethyl phthalate [MEP], mono-n-butyl phthalate [MnBP], mono-isobutyl phthalate [MiBP], mono-(3-carboxypropyl) phthalate [MCPP], mono-benzyl phthalate [MBzP], mono-2-ethylhexyl phthalate [MEHP], mono-(2-ethyl-5-hydroxyhexyl) phthalate [MEHHP], mono-(2-ethyl-5-oxohexyl) phthalate [MEOHP]) were measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Studies have consistently shown that changes in EDC concentrations and disease vary with length of US residence, although the direction of that change differs depending on the metabolite. One study [ 12 ] found higher MEP and MBP phthalate metabolite concentrations in foreign-born Asians (geometric mean: 22.8 and 8.4 ng/mL, respectively) than in US-born Asians (geometric mean: 16.9 and 4.4 ng/mL, respectively). These metabolite concentrations steadily decreased with longer US residence for immigrants and were almost indistinguishable to levels in US-born individuals for immigrants who resided in the US for over 30 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have consistently shown that changes in EDC concentrations and disease vary with length of US residence, although the direction of that change differs depending on the metabolite. One study [ 12 ] found higher MEP and MBP phthalate metabolite concentrations in foreign-born Asians (geometric mean: 22.8 and 8.4 ng/mL, respectively) than in US-born Asians (geometric mean: 16.9 and 4.4 ng/mL, respectively). These metabolite concentrations steadily decreased with longer US residence for immigrants and were almost indistinguishable to levels in US-born individuals for immigrants who resided in the US for over 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…EDC exposure and women’s reproductive health is understudied and not characterized well in Asian Americans, much less Chinese Americans. In studies that do include Asian Americans, their risk of GDM is particularly high, but urinary phthalate levels have actually been found to be lower in Asians than Blacks, Hispanics, and often times Whites as well [ 12 , 46 ]. Still, we see urinary MEP and MBP concentrations, which are related to GDM, change by length of US residence [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dealing with toxic trespass brings to light disputes between laypeople and professionals, citizens and governments, and among professionals, because the consequences of exposure are often poorly understood and because environmentally induced diseases are among the most prominent types of "contested illnesses" (Brown 2007). Toxic trespass often disproportionately impacts environmental justice (EJ) communities, because polluting facilities are concentrated in low-income communities and communities of color, and exposure to many chemicals through consumer products is also higher for marginalized populations (Helm et al 2018;Mitro et al 2018). Precisely because environmental diseases are so common in daily life and all aspects of the economy, these diseases have become highly politicized and have spurred much social movement activism.…”
mentioning
confidence: 99%